Investigating the cognitive processes in solving management science problems - Cheng, Sheila; Siow, Heng Loke (International Association of Technology, Education & Development, 2010)
Several studies on cognition processes especially in science and mathematics education (Yingxu Wang, & Chiew (2010): Sa’adah (2004): Lee (2003)) found that differences in cognition processes have an impact on problem solving. However, there was rather less of research of cognitive processes in problem solving conducted in the area of Management Science (MS) or Operations Research (OR). MS/OR is characterized by its broad applicability, from health care to logistics to financial services; and by a wide variety of career opportunities and work styles it embraces.